Covariance structure analysis of innovation and ICT use among Japanese innovative SMEs - Hiroki Idota; Teruyuki Bunno; Masatsugu Tsuji (International Telecommunications Society (ITS), 2013)
One of the common features of innovative SMEs identified from our previous surveys and in-depth interviews is innovation capability accumulated inside the firm, which enables them to create new products which meet customer needs and to cooperate with the other firms. The factors that SMEs achieve innovation are complex, and the causal relationships between factors have not been sufficiently clarified yet. This paper attempts to clarify the innovation process using covariance structure analysis, in particular focusing on the role ICT. Seven hypotheses are demonstrated by two models. The results obtained are as follows: (i) top management's participation and employee's motivation in the innovation process promote the effect of introducing ICT; (ii) this effect of ICT use raises innovation capability; in particular ability to connect external linkages; (iii) ICT use, innovation capability and external linkages enhance innovation activity; and (iv) effect of ICT use and innovation capability promote innovation directly. Thus this paper identifies that the effect of introducing ICT promotes innovation, and it is indispensable for innovation in Japanese SMEs.
Keywords: 330; ICT; Innovation; innovation capability; external linkages; covariance structure analysis